Czy Maurycy Mochnacki koncertował, grając na klawikordzie? Uwagi na marginesie wiersza Jana Lechonia - Wiśniewski, Jerzy (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The article deals with the question whether the poetic representation of the concert in the verse “Mochnacki” by Jan Lechoń is probable. There is some doubt about one of the elements making the world pictured in the verse - the instrument the protagonist is playing. We know the account given by a person present at the concert performed by Mochnacki in the Societé Philharmonique in Metz on March 23rd 1832 and that lets us point rather to a piano then to a clavickord as the instrument used for the concert. Our opinion is supported by the sound characteristics and the design of the instrument given by the poet in the verse. The clavickord is not able to achieve such a variety of musical expression as Jan Lechoń says Mochnacki could yield. There is a strong probability that the instrument was a piano but the poet called it a clavickord (by mistake or on purpose) for style reasons.